2018
DOI: 10.1021/acsaem.8b00909
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Conducting Polymer Nanowire–Tellurium Nanowire Composites

Abstract: In recent years, the thermoelectric properties of inorganic/polymer composites have been markedly improved. However, the enhancement mechanism in inorganic/polymer composites is still far from clear. In this work, we fabricate a novel type of thermoelectric composite by mixing high-mobility poly­(3,4-ethylenedioxythiophene) nanowire with tellurium nanowire and investigate the thermoelectric properties by varying the loading of tellurium nanowires and the underlying enhancement mechanism. We find that the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…As a potential high-performance thermoelectric material, conductive polymers exhibit unique advantages such as a low thermal conductivity, flexibility, lightweight, and efficient solution processability [9,[198][199][200][201][202]. However, more work needs to be done to further improve their thermoelectric performance to use them in flexible and wearable thermoelectric devices.…”
Section: D Materials In Polymer Thermoelectric Materialsmentioning
confidence: 99%
“…As a potential high-performance thermoelectric material, conductive polymers exhibit unique advantages such as a low thermal conductivity, flexibility, lightweight, and efficient solution processability [9,[198][199][200][201][202]. However, more work needs to be done to further improve their thermoelectric performance to use them in flexible and wearable thermoelectric devices.…”
Section: D Materials In Polymer Thermoelectric Materialsmentioning
confidence: 99%
“…If there is no electronic interaction between the two materials, the conductivity and Seebeck coefficient of the composites can be estimated in Composites with various inorganic TE materials and TE polymers were reported in literature, such as Bi 2 Te 3 /P3HT, 53,54 Bi 0.5 Sb 1.5 Te 3 /PEDOT:PSS, [55][56][57] Te/PANi, 58 and Te/PEDOT. 59 However, it is often observed that the Seebeck coefficient of these composites follow neither the series nor the parallel model. Carbon nanomaterials, particularly carbon nanotubes (CNTs) and graphene, are also popular fillers of TE polymers, such as CNTs/PEDOT:PSS, [60][61][62] CNTs/PANi, [63][64][65][66] and SWCNTs/P3HT.…”
Section: Energy Filtering Of Organic Te Composites With Nanofillersmentioning
confidence: 99%
“…Moreover, the challenge of combining rigid inorganic small molecules efficiently with polymers is a challenge [ 73 ]. Nevertheless, with the fabrication of nanowire-based OInTEs, there may be some applicability in the future for such materials into textile fiber-like form factors [ 257 ].…”
Section: Flexible Thermoelectric Materialsmentioning
confidence: 99%